A full Bayes before-after study accounting for temporal and spatial effects: Evaluating the safety impact of new signal installations. (September 2016) - Sacchi, Emanuele; Sayed, Tarek; El-Basyouny, Karim
Highlights: Neighboring road sites may share common network features and similar demographic/socio-economic characteristics that can lead to similar safety levels. Autoregressive models can be used to account for spatial interdependence among road sites. Accounting for temporal dynamics can also provide insights on how a safety treatment affects crash frequency over time. A before-after study accounting for spatial effects and temporal dynamics was conducted to evaluate the effectiveness of a road safety treatment. The impact on safety due to the installation of new traffic signals was assessed at 19 intersections in British Columbia (Canada). Abstract: Recently, important advances in road safety statistics have been brought about by methods able to address issues other than the choice of the best error structure for modeling crash data. In particular, accounting for spatial and temporal interdependence, i.e., the notion that the collision occurrence of a site or unit times depend on those of others, has become an important issue that needs further research. Overall, autoregressive models can be used for this purpose as they can specify that the output variable depends on its own previous values and on a stochastic term. Spatial effects have been investigated and applied mostly in the context of developing safety performance functions (SPFs) to relate crash occurrence to highway characteristics. Hence, there is a need for studies that attempt to estimate the effectiveness of safety countermeasures by including the spatial interdependence of road sites within the context of an observational before-after (BA) study. Moreover, the combination of temporal dynamics and spatial effects on crash frequency has not been explored in depth for SPF development. Therefore, the main goal of this research was to carry out a BA study accounting for spatial effects and temporal dynamics in evaluating the effectiveness of a road safety treatment. The countermeasure analyzed was the installation of traffic signals at unsignalized urban/suburban intersections in British Columbia (Canada). The full Bayes approach was selected as the statistical framework to develop the models. The results demonstrated that zone variation was a major component of total crash variability and that spatial effects were alleviated by clustering intersections together. Finally, the methodology used also allowed estimation of the treatment's effectiveness in the form of crash modification factors and functions with time trends.